2017
DOI: 10.1002/ejlt.201700300
|View full text |Cite
|
Sign up to set email alerts
|

Deep Eutectic Solvents Enable the Enhanced Production of n‐3 PUFA‐Enriched Triacylglycerols

Abstract: Efficient synthesis of n‐3 PUFA‐enriched triacylglycerol (TAG) by the esterification of glycerol with n‐3 PUFA in deep eutectic solvents (DES) is reported. There was a 1.2‐fold increase of TAG yield in DES compared with that in the solvent‐free system. Adsorption of the produced water by DES during esterification contributed to enhance the conversion efficiency by changing the reaction equilibrium. DES also served as an effective solvent for enriching the n‐3 PUFA of TAG in the upper layer of reaction media. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
(29 reference statements)
0
7
1
Order By: Relevance
“…The maximal n-3 PUFA-rich TAG content 55.8 with similar n-3 PUFA composition to the substrate was obtained at 12 h in CG system. There was a 1.38-fold increase of TAG content in CG system compared with that in the solvent-free system in this study, which was higher than that 1.2-fold at 48 h obtained by Novozym 435 in the literature 48 . It could be concluded that the catalytic efficiency of immobilized MAS1 lipase was better than that of Novozym 435.…”
Section: 3contrasting
confidence: 75%
“…The maximal n-3 PUFA-rich TAG content 55.8 with similar n-3 PUFA composition to the substrate was obtained at 12 h in CG system. There was a 1.38-fold increase of TAG content in CG system compared with that in the solvent-free system in this study, which was higher than that 1.2-fold at 48 h obtained by Novozym 435 in the literature 48 . It could be concluded that the catalytic efficiency of immobilized MAS1 lipase was better than that of Novozym 435.…”
Section: 3contrasting
confidence: 75%
“…10 On the basis of DESs, Dai et al ( 2013) 11 discovered that many plant abundant primary metabolites changed their state from solid to liquid when they were mixed in the proper ratio, resulting in the discovery of over 100 DESs from nature. 16 organic synthesis, 17 and electrochemistry. 18 Particularly, NADESs have been widely applied as the assisted extraction solvents for protein 16 and the thermal stability solvents of protein.…”
Section: Introductionmentioning
confidence: 99%
“…16 organic synthesis, 17 and electrochemistry. 18 Particularly, NADESs have been widely applied as the assisted extraction solvents for protein 16 and the thermal stability solvents of protein. 19 Specifically, Dai et al (2013) 20 declared that natural deep eutectic solvents formed by organic acid and sugar was a green approach for the dissolution of wheat proteins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to date, several enzymes such as lipases, proteases and epoxide hydrolases have shown great catalytic performance in DES, demonstrating their potential to replace ILs and/or organic solvents in biocatalytic reactions. Nevertheless, some questions remains to answer and an in-depth understanding on how DESs can activate and stabilize enzymes or how the biocatalysis products may actually be separated from DES will promote the application of DESs in biocatalysis to laboratory or industrial scale 8,13 .…”
Section: Scaled Up?mentioning
confidence: 99%